2019
DOI: 10.1016/j.jobcr.2018.05.006
|View full text |Cite
|
Sign up to set email alerts
|

The comparative evaluation of 1% alendronate gel as local drug delivery system in chronic periodontitis in smokers and non smokers: Randomized clinical trial

Abstract: Introduction: Periodontitis is a progressive disease of microbial origin involving the loss of supporting tissues of the teeth resulting from host inflammatory and immunologic reactions. The standard approach to the prevention and treatment of periodontal diseases for a number of years has been mechanical therapy and if required surgical intervention Researcher thought of creating a treatment modality where by altering the host response, the destructive host mechanisms could be interfered affecting the final o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
(33 reference statements)
1
4
0
2
Order By: Relevance
“…In addition, there was a statistically significant difference at 3 and 6 months in group II when compared to group I. These results are in agreement to Pradeep et al (2016) (24) and Sheokanda et al (2018) (25) who reported that topical application of alendronate showed a gain in bone density and improved bone mass after 6 m observational period.…”
Section: Bostanci Et Al (2007)supporting
confidence: 89%
“…In addition, there was a statistically significant difference at 3 and 6 months in group II when compared to group I. These results are in agreement to Pradeep et al (2016) (24) and Sheokanda et al (2018) (25) who reported that topical application of alendronate showed a gain in bone density and improved bone mass after 6 m observational period.…”
Section: Bostanci Et Al (2007)supporting
confidence: 89%
“…Following removal of duplicates and elimination based on title and abstract (Appendix Table 4), 108 full texts remained for further assessment. From those, 97 articles were excluded for various reasons, and thus 11 studies (Rocha et al 2004; Lane et al 2005; Graziani et al 2009; Sharma and Pradeep 2012a, 2012b; Pradeep et al 2013, 2017; Sharma et al 2017; Gupta et al 2018; Ipshita et al 2018; Sheokand et al 2019) were included in the qualitative synthesis. From the latter, the study by Graziani et al (2009) was omitted from the quantitative synthesis due to missing data that could not be retrieved.…”
Section: Resultsmentioning
confidence: 99%
“…From the latter, the study by Graziani et al (2009) was omitted from the quantitative synthesis due to missing data that could not be retrieved. Furthermore, the studies by Sharma and Pradeep (2012b), Sharma et al (2017), and Sheokand et al (2019) reported data on the basis of the assessed tooth sites rather than the examined patients and were thus included only in the qualitative evaluation to avoid bias due to pooling of different statistical units.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 A lo largo del tiempo, el tratamiento para la periodontitis fue puramente mecánico y/o quirúrgico; sin embargo, en la actualidad, se están buscando tratamientos alternativos que contribuyan a la regeneración ósea guiada. [4][5][6] Una de estas alternativas, como coadyuvante, es el uso de bifosfonatos, destacando el alendronato, el cual se ha comprobado que inhibe la producción de interleukina-1α (IL), IL-6 y TNF causada por los monocitos y la reabsorción ósea, desencadenando propiedades osteoestimulativas. [7][8][9] En un estudio realizado en las diáfisis del fémur del ratón, la aplicación directa de alendronato aceleró y promovió, localmente, la regeneración ósea, comportándose como material osteoinductivo; además mejoró la calidad de tejido óseo neoformado y la densidad del tejido óseo.…”
Section: Tema Central Del Estudiounclassified